2012
DOI: 10.1111/gcb.12025
|View full text |Cite
|
Sign up to set email alerts
|

Widespread decreases in topsoil inorganic carbon stocks across China's grasslands during 1980s–2000s

Abstract: Soil carbon (C) stocks consist of inorganic and organic components, ~1.7 times larger than the total of the C stored in vegetation and the atmosphere together. Significant soil C losses could thus offset any C sink in vegetation, creating a positive feedback to climate change. However, compared with the susceptible sensitivity of organic matter decay to climate warming, soil inorganic carbon (SIC) stocks are often assumed to be relatively stable. Here, we evaluated SIC changes across China's grasslands over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…Moreover, as a consequence of climate change, some projections suggest that erosion rates could increase by 25-55 % during the twenty-first century (Delgado et al 2013). In turn, the erosion of soil surface layers can also lead to the exposure of carbonates to climatic elements and acid deposition, aspects that could increase the loss of C from soils to the atmosphere (Lal 2004;Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a consequence of climate change, some projections suggest that erosion rates could increase by 25-55 % during the twenty-first century (Delgado et al 2013). In turn, the erosion of soil surface layers can also lead to the exposure of carbonates to climatic elements and acid deposition, aspects that could increase the loss of C from soils to the atmosphere (Lal 2004;Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The deposition rate of carbonate is relatively high in grassland soils with a high alkalinity and aridity (Lal, 2008;Yang et al, 2012), and hence SIC is the major form of soil carbon in many grasslands (Mi et al, 2008). SIC storage in China is approximately 53.3-77.9 Pg (Li et al, 2007;Mi et al, 2008), 54 % of which is mainly distributed in the temperate and alpine grasslands located in Inner Mongolia and the Qinghai-Tibetan Plateau (Mi et al, 2008).…”
mentioning
confidence: 99%
“…Our findings differed from these reports; we showed that pedogenetic sampling typically resulted in much higher SOC and SON than fixed-depth sampling (Table 2), which was 1.05-to 1.2-fold higher for SOC and SON storage and 1.2-to 1.4-fold higher for SOC and SON concentration. Pedogenetic sampling was also used in several major datasets in China (e.g., the 1979-1982 national survey) and has since become the main sampling method for nationwide evaluation of SOC and SON budgets [48][49][50]. Currently, however, more studies use the fixed-depth method for estimating SOC and SON storage in China [11,21,51].…”
Section: Sampling Methods Effects On Soc and Son Differ Between Their mentioning
confidence: 99%